The Importance of Parental Assistance in Supervising the Use of Technology for Children During the Home Learning Program - Dedi Riyan Rizaldi; Eris Nurhayati; Ziadatul Fatimah; Zakiya Amni (International Journal of Engineering, Science and Information Technology, 2021)
Writing this article aims to provide an overview of the role of parents when assisting children in using various technologies during the learning process from home. This is because without any limitations in technology it can have a good or bad impact on children if it is not used according to the required context. Therefore, the subject of the study to be discussed is more focused on the learning of children aged 7-15 years, who in the learning process still really need assistance from their parents. Writing this article is done through a process of literature review of various literature starting from the process of determining the topic of the problem, determining the type of data      collection method, collecting various data that support the topic, conducting the data analysis process, and drawing conclusions based on the data that has been obtained. Based on the data that has been obtained, the role of parents in assisting children to use technology while learning from home is very important, especially in maintaining and increasing children's motivation to continue learning.